The composite quality score for the appraisal of prospective controlled clinical therapy trials in systematic reviews and its limits - Mickenautsch, Steffen; Rupf, Stefan; Yengopal, Veerasamy (Frontiers in Medicine, 2023)
Systematic reviews of prospective controlled clinical therapy trials are one of the most important sources of information in modern medicine. Besides the systematic search for and statistical pooling of current clinical trial data for a particular type of therapy, systematic reviews also have the task of appraising the quality of trial results. The quality of trial results may be diminished by low internal trial validity, due to systematic error (bias). A high risk of bias may likely cause the reported trial results to be diverted from the actual true therapeutic effect and thus render it unsuitable for clinical guidance. According to the Cochrane Collaboration, the risk of bias in clinical therapy trials should be assessed using its Risk of Bias tool, Version 2 (RoB 2). However, the tool has been established to have poor inter-rater reliability, with a limited empirical evidence base and described as complex and demanding. Against this background, the Composite Quality Score (CQS) has been developed as a possible alternative trial appraisal tool, characterised by high epistemic rigour, empirical evidence base, inter-rater reliability and ease of use. This article presents the current evidence of the CQS and its limitations.